Beavers - Gish, Melissa (Mankato, MN : Creative Education, 2014)
"A scientific look at beavers, including their habitats, physical characteristics such as their gnawing teeth, behaviors, relationships with humans, and abundance of the rodents in the world today"--
Includes bibliographical references and index.
Keywords: Beavers -- Juvenile literature